Amalan Pengurusan Jepun Berdasarkan Teori Z - Ismail, Fadillah (Research in Management of Technology and Business, 2020)
The survival of an organization faces various risks and challenges is centered on the industrial relations that is co-driven by employees and employers in achieving the performance and goals set. This success has been proven in some of giant organizations in America and Japan, where they do not lie only in the quality of employees but also in their dynamic and comprehensive management style in managing organizations. Therefore, it is important to choose a management style that is not only accurate but ideal and effective to adapt and become a culture. This study attempts to highlight Theory Z which is one of the management approaches based on a combination of American and Japanese philosophical and characteristics to be considered in Malaysia organizational management.